Career Choice and Wage Growth - Pavan, Ronni (Journal of Labor Economics, 2011)
In this article, I present structural estimates of a search model that flexibly incorporates general human capital accumulation along with career and firm choice, where a career is empirically identified as a combination of industry and occupation. I use these estimates to empirically distinguish between the relative importance of various factors for generating wage growth over the life cycle. Evidence presented in the article highlights the importance of considering the two-stage search process that originates from the model. In particular, I demonstrate that previous instrumental variables methods dramatically underestimate the importance of firm-specific matches for wage growth.